2006
DOI: 10.1111/j.1439-0426.2006.00704.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in Bagre marinus (Ariidae) off Pernambuco, northeastern Brazil

Abstract: Throughout 1997, the catches of artisanal gillnetters working off the coast of northeastern Brazil were sampled monthly for Bagre marinus (Mitchill 1815). Significantly more females (n ¼ 207) than males (n ¼ 82) were caught, although there was no significant difference in their size compositions (21-47 cm fork length, FL). All males sampled (21-40 cm FL) had developed gonads and were classified as sexually mature. According to macroscopic and microscopic examination of their reproductive tract, females were se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
1
13
0
7
Order By: Relevance
“…Moreover, the egg size range for mouthbrooding males is similar to the range (0.7-1.9 cm) reported for the batch of largest eggs about to be spawned in mature female B. marinus (Mendoza-Carranza and Hernández-Franyutti 2005). Both Mendoza-Carranza and Hernández Franyutti (2005) and Pinheiro et al (2006) observed a positive linear relation between female size and the number of eggs about to be spawned. The former reported a minimum of 28 eggs in a female measuring 35 cm TL and a maximum of 60 eggs in a female measuring 57 cm TL, while the latter observed a minimum of 10 eggs in a female measuring 31 cm TL and a maximum of 33 eggs in a female measuring 45 cm TL.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, the egg size range for mouthbrooding males is similar to the range (0.7-1.9 cm) reported for the batch of largest eggs about to be spawned in mature female B. marinus (Mendoza-Carranza and Hernández-Franyutti 2005). Both Mendoza-Carranza and Hernández Franyutti (2005) and Pinheiro et al (2006) observed a positive linear relation between female size and the number of eggs about to be spawned. The former reported a minimum of 28 eggs in a female measuring 35 cm TL and a maximum of 60 eggs in a female measuring 57 cm TL, while the latter observed a minimum of 10 eggs in a female measuring 31 cm TL and a maximum of 33 eggs in a female measuring 45 cm TL.…”
Section: Discussionmentioning
confidence: 89%
“…Management measures are urgently needed, especially a total ban on purse seine fishing of mouthbrooding males. Pinheiro et al (2006) observaron una relación lineal positiva entre la talla de la hembra y el número de huevos próximos al desove. Los primeros autores registraron un mínimo de 28 huevos en una hembra de 35 cm LT y un máximo de 60 huevos en una hembra de 57 cm LT, y los últimos registraron un mínimo de 10 huevos en una hembra de 31 cm LT y un máximo de 33 huevos en una hembra de 45 cm LT.…”
Section: Discussionunclassified
“…A reprodução ocorre em diferentes épocas, mas principalmente relacionada aos meses mais quentes ou com maior aporte de águas interiores: do final da primavera ao início do verão para Genidens genidens em Jacarepaguá, Sepetiba e Maricá (Rio de Janeiro), Cananéia (São Paulo) e Guaratuba (Paraná) (Mishima & Tanji 1983b, Barbieri et al 1992, Chaves 1994, Araújo et al 1998a, Silva et al 1998, Mazzoni et al 2000, Gomes & Araújo 2004; na primavera e início do verão para Cathorops spixii em Sepetiba, Cananéia e baía dos Pinheiros (Paraná) (Mishima & Tanji 1983b, Fávaro et al 2005), e no verão e início do outono em Natal (Rio Grande do Norte) (Gurgel et al 2000); na primavera para Sciadeichthys luniscutis (=A. luniscutis) em Sepetiba (Gomes & Araújo 2004) e na primavera e verão em Cananéia (Mishima & Tanji 1983a); no outono para Bagre marinus na costa de Pernambuco (Pinheiro et al 2006); e no final da primavera e início do verão para Netuma barba (=G. barbus) no estuário da Lagoa dos Patos (Rio Grande do Sul) (Reis 1986).…”
Section: Introductionunclassified
“…A incubação ocorre no verão para Genidens genidens e há indicação de alimentação exógena das larvas durante a incubação (Chaves 1994), com duração de dois a três meses (Barbieri et al 1992). De maneira geral, a fecundidade é baixa e varia com as espécies, entre um mínimo de 7 e máximo de 38 ovócitos para G. genidens (Barbieri et al 1992, Araújo et al 1998a), de 11 a 22 para B. marinus (Pinheiro et al 2006), entre 6 e 24 para Sciadeichthys luniscutis (=A. luniscutis) (Gomes & Araújo 2004), entre 32 e 272 para Netuma barba (=G.…”
Section: Introductionunclassified
“…These reproductive strategies have a negative influence on populations' ability to recover, as egg development depends on oral incubation (Carvalho-Filho, 1999;Fávaro et al, 2005). Besides, all individuals of B. marinus were captured before reaching the size at first maturity; this might have happened because of this species' present late maturity (Pinheiro et al, 2006). The sum of these two parameters might have promoted this species' low resilience.…”
Section: Discussionmentioning
confidence: 99%